Automatic testing of GUI‐based applications. (29th May 2014) - Mariani, Leonardo; Pezzè, Mauro; Riganelli, Oliviero; Santoro, Mauro; Bertolino, Antonia; Labiche, Yvan
SUMMARY Testing GUI‐based applications is hard and time consuming because it requires exploring a potentially huge execution space by interacting with the graphical interface of the applications. Manual testing can cover only a small subset of the functionality provided by applications with complex interfaces, and thus, automatic techniques are necessary to extensively validate GUI‐based systems. This paper presents AutoBlackTest, a technique to automatically generate test cases at the system level. AutoBlackTest uses reinforcement learning, in particular Q‐learning, to learn how to interact with the application under test and stimulate its functionalities. When used to complement the activity of test designers, AutoBlackTest reuses the information in the available test suites to increase its effectiveness. The empirical results show that AutoBlackTest can sample better than state of the art techniques the behaviour of the application under test and can reveal previously unknown problems by working at the system level and interacting only through the graphical user interface. Copyright © 2014 John Wiley & Sons, Ltd.